Pengaruh Kompetensi Kepala Ruang terhadap Kepuasan Perawat Pelaksana di Rumah Sakit PKU Muhammadiyah Gamping - Dinda Auliasari; Moh. Afandi (Universitas Malahayati Lampung, 2026)
ABSTRACT Job satisfaction of staff nurses is a key factor influencing the quality of nursing services in hospitals. Head nurses play an important managerial role in coordinating nursing care, managing human resources, and creating a supportive work environment. Therefore, head nurse competency is often assumed to affect staff nurse job satisfaction, although previous studies have shown inconsistent results. This study aimed to determine the effect of head nurse competency on staff nurse job satisfaction at PKU Muhammadiyah Gamping Hospital. This study employed a quantitative approach with a non-experimental correlational design and a cross-sectional method. The population consisted of 338 respondents, including head nurses and staff nurses across 16 inpatient wards. A total of 183 respondents were selected using stratified random sampling based on the Slovin formula with a 5% margin of error. Data were collected using the Nurse Executive Competencies Assessment Tool (AONE) and the Minnesota Satisfaction Questionnaire (MSQ). Data analysis was conducted using univariate analysis and Spearman’s rho correlation test with a significance level of p 0.05. The results showed that head nurse competency was generally categorized as high across all competency indicators, while staff nurse job satisfaction was categorized as satisfactory. However, the Spearman’s rho correlation test indicated no significant effect between head nurse competency and staff nurse job satisfaction. Head nurse competency does not have a significant effect on staff nurse job satisfaction at PKU Muhammadiyah Gamping Hospital, indicating that job satisfaction is influenced by other factors such as remuneration systems, workload, work environment, organizational policies, and peer relationships. Keywords: Head Nurse Competency, Staff Nurse Job Satisfaction, Nursing Management, Hospital. ABSTRAK Kepuasan kerja perawat pelaksana merupakan faktor penting dalam menjaga mutu pelayanan keperawatan di rumah sakit. Kepala ruang memiliki peran strategis dalam mengelola sumber daya keperawatan dan menciptakan lingkungan kerja yang kondusif, sehingga kompetensinya sering dikaitkan dengan tingkat kepuasan perawat pelaksana. Namun, hasil penelitian terdahulu menunjukkan temuan yang beragam. Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi kepala ruang terhadap kepuasan perawat pelaksana di Rumah Sakit PKU Muhammadiyah Gamping.Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional non-eksperimental dan metode cross-sectional. Populasi penelitian berjumlah 338 responden yang terdiri dari kepala ruang dan perawat pelaksana di 16 bangsal. Sampel sebanyak 183 responden ditentukan menggunakan teknik stratified random sampling. Pengumpulan data dilakukan menggunakan instrumen Nurse Executive Competencies Assessment Tool (AONE) dan Minnesota Satisfaction Questionnaire (MSQ). Analisis data dilakukan secara univariat dan bivariat menggunakan uji korelasi Spearman dengan tingkat signifikansi p 0,05. Hasil penelitian menunjukkan bahwa kompetensi kepala ruang berada pada kategori tinggi dan kepuasan perawat pelaksana berada pada kategori puas. Namun, hasil uji korelasi Spearman menunjukkan tidak terdapat pengaruh yang signifikan antara kompetensi kepala ruang dan kepuasan perawat pelaksana. Kompetensi kepala ruang tidak berpengaruh signifikan terhadap kepuasan perawat pelaksana di Rumah Sakit PKU Muhammadiyah Gamping, sehingga kepuasan kerja perawat dipengaruhi oleh faktor lain di luar kompetensi kepala ruang Kata Kunci: Kompetensi Kepala Ruang, Kepuasan Perawat Pelaksana, Manajemen Keperawatan, Rumah Sakit.